2020
DOI: 10.1503/cmaj.200650
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation in patients with COVID-19

Abstract: 1 Prepare outside the patient's room: assign team roles, check equipment and review the airway strategy Limit the number of in-room team members depending on the patient's condition and delegate an outside-room "runner" to provide additional outside-room equipment and medications. The airway manager should be experienced enough to achieve greater than 85% first-pass success for endotracheal intubation. 1 The airway strategy includes preoxygenation, positioning, endotracheal intubation and a clear plan for resc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Some protective measures and protocols are recommended for the intubation of patients diagnosed with COVID-19 (11)(12)(13). Using intubation boxes to prevent droplet spread, performing procedures in isolation rooms suitable for airborne infections, performing intubation practices with a separate special team, and only necessary personnel enter the operation room, cleaning and disinfection of the room after the procedure and the use of personal protective equipment (PPE) are some of these (11,12). In particular, the use of WCE and the participation of a limited number of personnel in the procedure are important, and it was observed that these precautions were explained in all videos that talked about intubation in a patient with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Some protective measures and protocols are recommended for the intubation of patients diagnosed with COVID-19 (11)(12)(13). Using intubation boxes to prevent droplet spread, performing procedures in isolation rooms suitable for airborne infections, performing intubation practices with a separate special team, and only necessary personnel enter the operation room, cleaning and disinfection of the room after the procedure and the use of personal protective equipment (PPE) are some of these (11,12). In particular, the use of WCE and the participation of a limited number of personnel in the procedure are important, and it was observed that these precautions were explained in all videos that talked about intubation in a patient with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Complete the procedure with the placement of a nasogastric probe. 7 Only if extremely necessary and with difficulty after three intubation attempts, declare the INTUBATION FAILURE and follow the DAS 2018 guidelines.…”
Section: Anesthesiamentioning
confidence: 99%
“…Research 5H/5T (hypovolemia, hypoxia, hydrogen ions, hypoglycemia, hypothermia; buffering, pneumothorax, pulmonary thromboembolism, coronary thrombosis, toxic/ trauma). 7,8 In children:…”
Section: If In Rhythm Not Shockable (Pea/asystole)mentioning
confidence: 99%
“…The diagnosis of COVID-19 was dependent on a positive reverse transcription-polymerase chain reaction test from nasal swab, pharyngeal swab, or sputum samples con rming the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [7]. If an intubator had a con rmed COVID-19 infection up to 30 days after intubation, it was considered "intubator infection.…”
Section: De Nitionsmentioning
confidence: 99%
“…Patients with coronavirus disease 2019 (COVID-19) sometimes require emergency intubation for mechanical ventilation [1][2][3]. Given the risks of infection transmission, several protocols and safety devices are recommended for use in this context [4][5][6][7]. To date, there have only been two observational studies regarding emergency tracheal intubation by anesthesiologists in China [8,9], one prospective study from the UK [10], and one international cohort study among emergency physicians [11], though only 1.6% of patients with COVID-19 underwent tracheal intubation in the latter study.…”
Section: Introductionmentioning
confidence: 99%